Identifying cultural ecosystem services of urban green infrastructure - Report about a pilot project undertaken in Lower Austria. - Rottenbacher, Christine; Cassidy, Tim (My University, 2014)
The Lower Austrian "Wohnbauforschung" has funded the pilot project in Laa an der Thaya to investigate ecosystem services of urban green infrastructure. This article focuses on our identification of cultural ecosystem services. This pilot project aims on the one hand to enhance the understanding of ecosystem service benefits of green infrastructure and on the other to strengthen the potential for the implementation of green. Urban green infrastructure included all public spaces, urban forests and parks. We considered green infrastructure as a network integrating a broad range of quality green places, designed and managed to enhance the character of place, while providing multiple benefits of ecosystem services. Our investigations at selected places represent a place-based scale where it is possible for humans to perceive and understand effects of climate change, as well as the benefits of urban green infrastructure. Within this approach the perceived cultural ecosystem services of the stakeholders were incorporated with a survey of existing ecosystem services (CO2 storage, rainwater management and urban heat island effects) to estimate the benefits from green infrastructure. This would lead to the initial development of modules to implement and enhance the urban green infrastructure in Laa. To overcome the barriers to implement green infrastructure an integrated approach has been developed together with a core stakeholder group. The "cultural services" were investigated in a public participation process, the Moved Planning Process or "MPP", in conjunction with a SWOT analysis to strengthen reflection and appreciation of the natural benefits of urban green infrastructure systems. In a dialogue about cultural ecosystem services and the multiple benefits of green infrastructure we defined together "special " areas, i.e. areas that are of a particular value, e.g. for recreation, as meeting places, but also available places wherein green infrastructure can be implemented.
Keywords: Stadtplanung; Wohnungswesen; Infrastruktur; Freiraum; Stadtökologie; Stadtbegrünung; Ökosystem; Naherholung; Lebensqualität; Gesundheit; Datenerfassung; Messung; Pilotprojekt